Announcement of convertible debt issuance, capital structure change and signaling: a comparative study for the Athens Stock Exchange - Καινούργιος, Δημήτριος Φ. (SPOUDAI Journal of Economics and Business, 2003)
This paper provides evidence on the valuation effects of the announcement of convertible debt issuance by Greek companies listed in the Athens Stock Exchange (ASE) during '90. The price effects of the announcement of convertible debt offerings are compared with those of other major capital structure changes (announcement of straight debt and common stock issuance). View in this broader context, it is empirically investigated the signaling mechanism of the Greek stock market, and it is also tested the semi-strong efficient market hypothesis. The evidence suggests that the announcement of convertible and straight debt offerings have both positive and negative price effects, while the announcement of common stock issuance have negative price effects. The nature of the conveyed information about the issuing firms is consistent with other international evidence and gives support (total or partial) to specific classes of capital structure theories, while the existence of non-zero abnormal returns around the announcement periods leads to the rejection of the semi-strong efficient market hypothesis for the ASE JEL Classification: G14